2015
DOI: 10.1021/acs.biomac.5b00550
|View full text |Cite
|
Sign up to set email alerts
|

Cholesterol Modified Self-Assemblies and Their Application to Nanomedicine

Abstract: Cholesterol is a ubiquitous molecule in biological systems, and in particular plays various important roles in mammalian cellular processes. The presence of cholesterol is integral to the structure and behavior of biological membranes, and profoundly influences membrane involvement in cellular mechanisms. This review focuses on the incorporation of cholesterol into synthetic nanomaterials and assemblies, focusing on LC phase behavior, morphology/self-organization and hydrophobic interactions, all important fac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
66
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 92 publications
(71 citation statements)
references
References 366 publications
(578 reference statements)
1
66
0
Order By: Relevance
“…The effect of addition of cholesterol on PNA loading efficiency was evaluated for all the phospholipids selected for this study, using amounts of cholesterol ranging from 10 to 47 mol%. It is well-known that the insertion of cholesterol can cause an opposite effect on the lipid bilayer fluidity depending on the T m value of the neighboring phospholipids (28). Above the T m , the interaction of rigid cholesterol molecules with hydrocarbon tails of phospholipids causes a stiffening of the lipid bilayer, which becomes less permeable to small water-soluble molecules.…”
Section: Drug Loadingmentioning
confidence: 99%
“…The effect of addition of cholesterol on PNA loading efficiency was evaluated for all the phospholipids selected for this study, using amounts of cholesterol ranging from 10 to 47 mol%. It is well-known that the insertion of cholesterol can cause an opposite effect on the lipid bilayer fluidity depending on the T m value of the neighboring phospholipids (28). Above the T m , the interaction of rigid cholesterol molecules with hydrocarbon tails of phospholipids causes a stiffening of the lipid bilayer, which becomes less permeable to small water-soluble molecules.…”
Section: Drug Loadingmentioning
confidence: 99%
“…Moreover, HPMA monomers can be copolymerized with various comonomers, which opens a way to introduce biologically active molecules into the polymer structure, for example, drugs, various labels, or targeting molecules . The anchoring group was chosen to be cholesterol as it is a natural component of biological membranes . Modification of PC liposomes by biocompatible pHPMA ensures the biocompatibility of the entire construct, a liposome‐pHPMA carrier.…”
Section: Introductionmentioning
confidence: 99%
“…1119 Modification with hydrophobic moieties such as cholesterol or hydrophobic drugs allows for assembly of the polysaccharides into nanoparticles that may improve the efficacy and safety of drug delivery. 20, 21 For example, modifying HES with fatty acids allowed for assembly of HES micelles, 22 and subsequently it was shown that propylating starch facilitates the assembly of large nanoparticles for encapsulation of doxetaxel. 23 Using pentadecylphenol-modified dextran, Pramod et al synthesized a dual delivery nanovesicle of camptothecin and doxorubicin, which displayed synergistic improvement in anticancer activity.…”
Section: Introductionmentioning
confidence: 99%